Pengaruh Komitmen Organisasi, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan - Deny Kurniawan; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTBased on research conducted with the aim of analyzing the effect of Organizational Commitment and Work Environment Organizational Commitments on Employee Performance in Malang Municipal Water Supply Company. The population in this study were 325 employees of PDAM Malang City. The sampling technique used is proportional stratified random sampling in which the technique is to select samples based on class. The analytical method used in this study is multiple linear regression analysis with hypothesis testing using the t test and f test. From this study produced answers that have been previously processed that simultaneously the Organizational Commitment of Work Discipline and Work Environment influences Performance, Organizational Commitment influences Performance, Work Discipline influences Performance, and Work Environment influences Performance.Keywords: Organizational Commitment, Work Discipline, Work Environment, Performance